“Uncertain as to future fate”: 1837 Upper Canadian rebels incarcerated in “John Montgomery’s Room” in Toronto’s jail in 1838 - Raible, Chris (Ontario History)

(untitled) (The Ontario Historical Society, 2021)
Through first-hand accounts, most notably that of prisoner John Goldsworthy Parker, this article examines the lives of the men who were imprisoned following their failed rebellion in 1837 in Upper Canada. As a close camaraderie developed, they began to think of themselves as the men in “John Montgomery’s Room” (named after the owner of the tavern where the rebels had rallied in the Rebellion). Included are descriptions of their daily lives, how they interacted, their meals, devotions, sicknesses, and entertainments, how they coped with the execution of some of their fellow prisoners, and, most closely, the carving of many unique commemorative boxes many of which remain today as artifacts of the failed rebellion.